Dockers in Las Palmas: Technological changes, institutional evolution and waterfront radicalism (1960-2009) - Daniel Castillo Hidalgo; Miguel Suárez Bosa (Nuevo mundo - Mundos Nuevos, 2016)
Container shipping has constituted a revolution in trade on a planetary scale. Ports have had to change their infrastructures in order to incorporate the requisite technology, which has modified the historical trade networks around the World. The port of Las Palmas (Canary Islands) adapted its infrastructures and its institutional environment in order to develop the container activity that was added to its historical functions as scale port. The main aim of this paper is to explore the changes in port labour organization through the progressive implementation of container activities in Las Palmas. Port activity indicators, regulation, port infrastructures and labour relationships will be analysed with a view to presenting an overall perspective of the changes that have taken place in dock labour since the 1960s.